Proxy mineral magnetic and elemental analyses for 2004 tsunami impact deposit along the Muttukadu backwater, East Coast of India: Scope of the palaeotsunami studies. (25th February 2019) - Basavaiah, N.; Mahesh Babu, J.L.V.; Prizomwala, S.P.; Achyuthan, H.; Siva, V.H.R.; Boral, Pranab
Abstract: Following the line of approach enumerated in the tsunami toolkit of Chagué-Goff et al. (2011), 'Expanding the proxy toolkit to help identify past events - Lessons from the 2004 Indian Ocean Tsunami and the 2009 South Pacific Tsunami, Earth Sci. Rev. 107 (1–2), 107–122', measurements of elemental and mineral magnetic properties coupled with textural parameters have been used to evaluate the 2004 Indian Ocean Tsunami (IOT) induced sediments on the Muttukadu backwaters, East Coast of India. To investigate the sediment provenance, specific Fe, Mn and Pb elemental concentrations were measured in surface sediments and compared with the previously published pre-tsunami database of backwater/inner continental shelf sediments. We found the enrichment of Fe and Pb, against depletion of Mn concentration in present tsunami sediments as compared with pre-tsunami Muttukadu sediments, reflecting the variation of the sediment source area. However, the present data of Fe and Pb enrichment and Mn depletion correlates well with continental shelf sediments hinting at sedimentary routes, processes of erosion and wave propagation. The studied tsunami deposits are characterized by dominant ∼40–85% coarse sand fractions and higher proportion of detrital low and high coercivity Fe-Ti oxides, such as magnetite, titanomagnetite and hematite, reflected by magnetic concentration (magnetic susceptibility (χ), anhysteretic remanent magnetization (ARM)) and coercivity-dependent parameters (soft isothermal remanent magnetization (Soft IRM), Hard IRM, magnetomineralogical S-Ratio and saturation IRM (SIRM)). So, it can be shown that the random spatial variability and the inverse relationship between magnetic concentration χ, ARM and SIRM parameters and grain-size ARM/χ, SIRM/χ and ARM/SIRM ratios as diagnostic criteria for the tsunami impacted the distribution of magnetic parameters in coastal backwater environments. Contrasting mineral magnetic and geochemical properties together with more sand (mean 65%) when compared with silt (mean 25%) content in tsunami sediments indicates that the area was affected by high-energy tsunami waves. The study validates environmental magnetism as a proxy, which is fast and robust for identifying the tsunami or palaeotsunami deposits.